2006
DOI: 10.1080/22201009.2006.10872136
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected glucose abnormalities in patients with coronary artery disease

Abstract: P Rheeder, MB ChB, MMed (Int Med), FCP (SA), MSc (Clin Epidemiol), PhD Corresponding author : P Soma (psoma@med.up.ac.za)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This indicates that females are at increase risk as compared to males, which can be attributed to the sedentary lifestyle with very little physical activity with increase westernization among females. A cross-sectional, diagnostic study undertaken by Soma and Rheeder [30] in Pretoria Academic Hospital found the overall incidence of diabetes to be 11.7%. Our study prevalence is low compared to this basically because ours is a population base study whiles that of Soma and Rheeder was done on in-patients.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that females are at increase risk as compared to males, which can be attributed to the sedentary lifestyle with very little physical activity with increase westernization among females. A cross-sectional, diagnostic study undertaken by Soma and Rheeder [30] in Pretoria Academic Hospital found the overall incidence of diabetes to be 11.7%. Our study prevalence is low compared to this basically because ours is a population base study whiles that of Soma and Rheeder was done on in-patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 120 patients with suspected coronary artery disease (CAD) (mean age 58 years), according to the WHO criteria the prevalence of diabetes was found to be 11.7% (Soma and Rheeder, 2006). It was reported that most of these subjects with diabetes would not have been detected (9 out of 14) had an OGTT not been used (ADA criteria).…”
Section: Hmentioning
confidence: 99%